2020
DOI: 10.1080/09553002.2020.1767817
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged effect associated with inflammatory response observed after exposure to low dose of tritium β-rays

Abstract: Background: The value of relative biological effectiveness of tritium increases at low dose domain, which results in the suspicion of weighting factor of 1 for tritium after low dose exposure. Thus, present study was carried out to analyze the differences in the cellular responses at early and late period between low dose of tritium b-rays and c-rays radiation. Methods: MCF-10A cells were exposed to low dose of tritium b-rays or c-rays, then cellular behaviors, such as DNA double strand breaks (DSBs), apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This also makes it an ideal candidate for future adoption of this model for tritiated particles, as discussed later. The persistent inflammatory response measured after exposure of mammary epithelial cells to low-dose tritium was hypothesized to be related to accumulation of tritium in the form of OBT in cellular DNA or lipids (20), though intracellular activity is measured to be very low in our case. Also, it was recently shown that, on HUVEC cells exposed to HTO (3.7 and 3,700 kBq/ml), the increase of IL-8 secretion could play a pivotal role in cell defense (21).…”
Section: Discussionmentioning
confidence: 69%
“…This also makes it an ideal candidate for future adoption of this model for tritiated particles, as discussed later. The persistent inflammatory response measured after exposure of mammary epithelial cells to low-dose tritium was hypothesized to be related to accumulation of tritium in the form of OBT in cellular DNA or lipids (20), though intracellular activity is measured to be very low in our case. Also, it was recently shown that, on HUVEC cells exposed to HTO (3.7 and 3,700 kBq/ml), the increase of IL-8 secretion could play a pivotal role in cell defense (21).…”
Section: Discussionmentioning
confidence: 69%
“…Shi et al found that ROS could induce the expression of SOX2 under hypoxia and then activated the activation of Wnt/ β -catenin, thus promoting the EMT of HacaT cells [ 45 ]. Quan et al proved that tritium β -rays could lead to increased ROS and the occurrence of an inflammatory reaction in breast epithelial cell line McF–10a cells [ 46 ]. Therefore, we hypothesized that the up-regulation of the Wnt pathway induced by tritiated water was related to ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a high level of ROS and an increase in the number of DNA double strand breaks were found in MCF-10 cells exposed to low doses of HTO [ 49 ]. Another study reported that DNA strand breaks induced by HTO in human umbilical vein endothelial cells, assessed by comet assay and γ-H2AX immunostaining, were associated with modulations of DNA repair that could be regulated by the c-myc gene expression via miR34a [ 46 ].…”
Section: Discussionmentioning
confidence: 99%